Anthelmintic Efficacy against the Prevalent Gastrointestinal Parasite in Cattle - Athuraliya, N.G.; Piratheepan, S. (University of Jaffna, 2021)
Gastrointestinal parasitic infections are a major constraint in cattle management. Twenty cattle (n=20) were randomly selected and divided into different groups as treatment group and control group. Treatment group had 15 number of animals and control group had 5 animals. The treatment group was divided into three different categories based on the age as 5 animals in each group (< 1 ½ year age, 1 ½ - 3 years age, > 3 year age) and group of cattle did not separate into groups was considered as the control group. Then anthelmintic treatment was given according to the body weight using Albendazole (10 mg/kg). Thereafter, fecal samples were collected from each animal every two weeks until 10th week of post treatment. Each fecal sample was examined using McMaster technique to count the parasitic eggs per gram (EPG). Data was analyzed using SPSS univariate method. The highest (p<0.05) egg count was observed in the initial stage (before giving treatment) and it was more than 1500 EPG. Two weeks after the treatment marginal means of egg count was reduced suddenly and it was less than 500 EPG (p<0.05). The 4th week after treatment also shown a reduction in egg count than the 2nd week after treatment. The least marginal means of egg count was shown by the 4th week after treatment (p<0.05). Thereafter the marginal means of egg count was started to raised. At the eighth weeks after treatment the egg count was increased than previous week and it was less than the 500 EPG (p<0.05). 10th weeks after treatment egg count was increased than previous weeks. Thus, it can be concluded as Albendozole oral administration was effective to control gastrointestinal parasites until 4th weeks and it was strongly recommended to treat the animals regularly of every 8 weeks interval.
Keywords: Anthelmintic; Cattle; McMaster egg counting; Parasitism